Analisis Motivasi Belajar Peserta Didik Sekolah Dasar pada Pembelajaran IPAS melalui Teknik Penguatan (Reinforcement) dengan Model Problem Based Learning - Sofyani, Annisa; Wahyuni, Holy Ichda; Afiani, Kunti Dian Ayu (Universitas Nusantara PGRI Kediri, 2025)
This study aims to analyze the learning motivation of students in learning Natural and Social Sciences (IPAS) through reinforcement techniques with the Problem Based Learning (PBL) model. This study uses a qualitative descriptive approach with data collection methods in the form of observation, interviews, and documentation. The research subjects included classroom teachers and students of class V. The results of this study showed that the application of reinforcement techniques in the PBL model increased the enthusiasm and active participation of students from the beginning to the end of the learning process. In addition, reinforcement techniques help students better understand the material being taught and have a positive impact on the final summative results obtained. In conclusion, reinforcement techniques combined with the PBL model can be an effective method that can be applied by teachers to help students' motivation to learn in the classroom.